Neuropilin-1: A Key Protein to Consider in the Progression of Pediatric Brain Tumors - Douyère, Manon; Chastagner, Pascal; Boura, Cédric (Frontiers in Oncology, 2021)
Neuropilins are transmembrane glycoproteins that play important roles in cardiovascular and neuronal development as well as in immunological system regulations. NRP1 functions as a co-receptor, binding numerous ligands such as SEMA 3 or VEGF and, by doing so, reinforcing their signaling pathways, but can also interface with the cytoplasmic protein Synectin. NRP1 is expressed in many cancers, such as brain cancers, and is associated with poor prognosis. The challenge today for patients with pediatric brain tumors is to improve their survival rate while minimizing the toxicity of current treatments. The aim of this review is to highlight the involvement of NRP1 in pediatric brain cancers, focusing essentially on the roles of NRP1 in cancer stem cells and in the regulation of the immune system. For this purpose, recent literature and tumor databases were analyzed to show correlations between NRP1 and CD15 (a stem cancer cells marker), and between NRP1 and PDL1, for various pediatric brain tumors, such as high- and low-grade gliomas, medulloblastomas and ependymomas. Finally, this review suggests a relevant role for NRP1 in pediatric brain tumors progression and identify it as a potential diagnostic or therapeutic target to improve survival and life quality of these young patients.